The big bang theory. The complete second season [videorecording (DVD)] - Galecki, Johnny; Cuoco, Kaley; Parsons, Jim, 1973-; Helberg, Simon; Nayyar, Kunal; Gilbert, Sara, 1975- (Big Bang Theory, 2009)
Physicists Leonard and Sheldon understand everything from the inescapable gravitational pull of a black hole to the intricate structure of the atom. But take those atoms and assemble them into a woman, and their comprehension comes to a grinding halt. This season, Leonard gets a girl. So does Sheldon. (Sheldon?!), Howard drives the Mars Rover into a ditch, Raj woos a terminator, gorgeous girl-next-door Penny falls under the spell of Age of Conan, and super-smart, uberconfident Leslie Winkler reduces mere men to spineless jellyfish. Includes all 23 episodes, plus never-before-seen featurettes.